KONTRIBUSI PEMBINAAN KEPALA KEMENTERIAN AGAMA DAN KOMPETENSI PENGAWAS TERHADAP PELAKSANAAN KOMPETENSI PROFESIONAL GURU PAI - Faisal, Faisal (TARBAWY : Indonesian Journal of Islamic Education, 2021)
Abstract. This study aims to determine the contribution of the guidance of the head of the Ministry of Religious Affairs and the competence of supervisors to the implementation of the professional competence of Islamic Religious Education (IRE) teachers. The method used in this research is quantitative analysis based on statistical inferential models. The data collection was done using observation, interviews, and questionnaires. After the data is collected, it is then processed using logical analysis for qualitative and statistical analysis for quantitative data using descriptive statistics, regression, and correlation. Based on the hypothesis test, the guidance of the Head of the Ministry of Religious Affairs and the competence of supervisors contributes positively and significantly to the implementation of the professional competence of Islamic Religious Education (IRE) teachers.Abstrak. Penelitian ini bertujuan untuk mengetahui kontribusi pembinaan kepala Kementerian Agama dan kompetensi pengawas terhadap pelaksanaan kompetensi profesional guru Pendidikan Agama Islam (PAI). Metode yang digunakan dalam penelitian ini adalah analisis kuantitatif berbasis model statistika inferensia. Adapun pengumpulan datanya dilakukan dengan menggunakan teknik observasi, wawancara, dan angket. Setelah data terkumpul, kemudian diolah dengan menggunakan analisis logika untuk kualitatif dan analisis statistika untuk data kuantitatif dengan menggunakan statistik deskriptif, regresi, dan korelasi. Berdasarkan uji hipotesis, pembinaan Kepala Kemenag dan kompetensi pengawas berkontribusi secara positif dan signifikansi terhadap pelaksanaan kompetensi profesional guru PAI.